A new Puddle Frog, genus Phrynobatrachus (Amphibia: Anura: Phrynobatrachidae), from the eastern part of the Upper Guinea biodiversity hotspot, West Africa - Kpan, Tokouaho Flora; Kouamé, N’goran Germain; Barej, Michael F.; Adeba, Patrick Joël; Emmrich, Mike; Ofori-Boateng, Caleb; Rödel, Mark-Oliver (Zootaxa, 2018)
We describe a new species of Phrynobatrachus from swamp forests in the southern border region of Ivory Coast and Ghana. The new species differs from all other known West African Phrynobatrachus by the combination of adult snout-vent-length being between 20 and 30 mm; absence of a spiny tubercle on the eyelid; presence of a dark face mask; a black throat in adult males; narrow and partly indistinct scapular ridges or comma shaped warts; distinct spinulae on males’ throats and dorsal surfaces; pronounced pedal webbing; round finger- and toe tips, not enlarged to discs; a white belly with small blackish spots in both sexes; more than one wide dark cross bar on hind legs; and rosé to reddish colour on ventral parts of hind legs in both sexes. It is further defined by its genetic and acoustic characters. It is morphologically and genetically most similar to P. liberiensis and P. intermedius.